Chemerin levels in chronic kidney disease: A systematic review and meta-analysis - Behnoush, Amir Hossein; Shobeiri, Parnian; Bahiraie, Pegah; Amirkhani, Nikan; Khalaji, Amirmohammad; Peiman, Soheil (Frontiers in Endocrinology, 2023)
Introduction: Chemerin as an inflammatory biomarker has gained attention in its biomarker capability. Several studies measured its levels in chronic kidney disease (CKD), as one of the common non-communicable causes of mortality and morbidity. Hence, this systematic review and meta-analysis aimed to investigate this association. Methods: PubMed, Scopus, Embase, and the Web of Science databases were systematically searched for studies investigating chemerin levels in any CKD stage (including end-stage renal disease patients undergoing hemodialysis (HD)) and comparing it with healthy controls. Random effect meta-analysis was performed to calculate the standardized mean difference (SMD) and 95% confidence interval. Results: A total of eight studies were included, comprised of 875 individuals, with a mean age of 56.92 ± 11.78 years. All studies had high quality based on the New-Castle Ottawa Scale (NOS). Meta-analysis revealed significantly higher levels of chemerin in CKD patients compared to healthy controls (SMD 2.15, 95% CI 0.83-3.48, p-value<0.01). Additionally, HD patients had statistically higher levels of chemerin than controls (SMD 2.10, 95% CI 0.58-3.62, p-value=0.01). In meta-regression, publication year accounted for 23.50% and 24.17% of heterogeneity for these analyses, respectively. Conclusion: Chemerin can be potentially used as a biomarker rising in CKD patients, which can suggest the inflammatory pathways for the disease. Further research is warranted for the assessment of its clinical applications and enlightening its role in the pathophysiology of CKD.